The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1136/adc.76.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of milk and maize based diets in kwashiorkor

Abstract: The dual sugar test of intestinal permeability is a reliable non-invasive way of assessing the response of the small intestinal mucosa to nutritional rehabilitation. Aim-To compare a local mix of maizesoya-egg to the standard milk diet in the treatment of kwashiorkor. Design-The diets were alternated three monthly in the sequence milk-maizemilk. There were a total of 533 kwashiorkor admissions of at least five days during the study who received either milk or maize. Intestinal permeability was assessed at week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Recent research conducted within the context of usual practice in Malawian NRUs has demonstrated the superiority of milk over maize-based diets for treating kwashiorkor and suggested the importance of micronutrients in reducing mortality. 2,21,22 The introduction of appropriate treatment protocols in refugee situations has reduced mortality in severely malnourished children, in some situations to less than 5%. 23 However, there are many confounding variables that need to be considered when comparing treatment response in a humanitarian emergency to the circumstances of presentation and management in a long-established NRU.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research conducted within the context of usual practice in Malawian NRUs has demonstrated the superiority of milk over maize-based diets for treating kwashiorkor and suggested the importance of micronutrients in reducing mortality. 2,21,22 The introduction of appropriate treatment protocols in refugee situations has reduced mortality in severely malnourished children, in some situations to less than 5%. 23 However, there are many confounding variables that need to be considered when comparing treatment response in a humanitarian emergency to the circumstances of presentation and management in a long-established NRU.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent Guatemalan study34 has reported high failure rates in non-acutely ill children of 31.6% (73 of 231). In permeability studies in Malawi,15 35 one author (DRB) encountered similar difficulties with urine collection in kwashiorkor cases and resorted to overnight urine collection, when urine bags were less likely to come off. From the additional experience in the Darwin setting, we conclude that L–R testing on urine is not a feasible outcome measure for a clinical trial in young children with diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 149 children with kwashiorkor in whom permeability testing was done, 76 were treated with a milk based diet, 64 with an exclusively maize based (milk free) diet, and nine with both diets over a changeover period. Details of the diets are given in the companion paper 16 . Clinical sepsis was defined as fever, respiratory distress, a change in mental status, shock or any abrupt deterioration in condition.…”
Section: Methodsmentioning
confidence: 99%